Further Evidence on the Effect of Clean Indoor Air Laws on Smoking: The Italian Case. - Celidoni, Martina; Pieroni, Luca; Salmasi, Luca (Southern Economic Journal, 2020)
The evidence about the effectiveness of anti‐smoking legislation on smoking behavior is mixed. We provide new estimates for Italy using unexplored data drawn from the Household Budget Survey. We show that the smoking ban introduced in 2005 has a significant effect on smoking incidence. According to our baseline specification, the ban reduces household‐based smoking prevalence by 1.3 percentage points. Results are robust to the various empirical strategies proposed in the literature, even accounting for seasonality.